Commonwealth [compact disc, unabridged] - Patchett, Ann (Harper Audio, 2016)
Commonwealth is the story of two broken families and the paths their lives take over the course of 40 years, through love and marriage, death and divorce, and a dark secret from childhood that lies underneath it all.